HG0.8CD0.2TE GROWN BY LIQUID-PHASE EPITAXY USING CD0.94ZN0.06TE BUFFER LAYER - KWAK, NJ; CHOI, IH; LIM, SW; SUH, SH (ELSEVIER SCIENCE BV, 1994)
Buffered structures of Hg0.8Cd0.2Te/Cd0.94Zn0.06Te/Cd0.97Zn0.03Te were grown by a slider LPE technique and their material properties were compared with those of Hg0.8Cd0.2Te/Cd0.97Zn0.03Te structures which have no buffer layer. Photoluminescence spectroscopy (PL) was used to determine the compositions of the buffer layers and the substrates and analyse the impurities in the buffer layers. Auger electron spectroscopy (AES) was used to analyse impurities. Either sodium or lithium related donor-acceptor pair (DAP) peaks were observed in the substrate, but not in the Cd0.94Zn0.06Te buffer layer. AES analysis revealed that the substrate contained some impurities such as Si, Al, O, K, Fe, and Mg. In the Cd0.94Zn0.06Te buffer layer, the above impurities were not detected. The distribution of dislocations in the epi-layers were analysed by defect etching as well as double crystal X-ray diffraction. For the buffered structure, most misfit etch-pits were located just above the interface between the Hg0.8Cd0.2Te and Cd0.94Zn0.06Te buffer, and their density was much lower than that in the unbuffered structure, in which etch-pits were distributed rather broadly in the epi-layer. Electrical properties of the Hg1.8Cd0.2Te epi-layers, which were Hg-annealed at 250-degrees-C, were analysed by Hall measurement at 77 K. The buffered structure showed the carrier concentrations of 7 X 10(13) to 1 X 10(14) cm-3 and Hall mobilities of 2 to 5 X 10(5) cm2/V.s.
Keywords: MOLECULAR-BEAM EPITAXY; CADMIUM TELLURIDE; CDTE; PHOTOLUMINESCENCE; IMPURITIES; BEHAVIOR; CRYSTALS